Ina, Moon: Geologic setting, scientific rationale, and site characterization for a small planetary lander concept. (July 2019) - Stopar, Julie D.; Lawrence, Samuel J.; Graham, Lee; Hamilton, Joseph; Denevi, Brett; John, Kristen K.; Meyer, Heather M.; Gruener, John E.; Núñez, Jorge I.; Draper, David S.; Maas, Bryan J.; Greenberg, Jacob M.
Abstract: The Ina Irregular Mare Patch (IMP) in the central lunar nearside (18.7°N, 5.3°E) is a small, two-by-three-kilometer exposure of uncommon volcanic deposits. The unusually well-preserved deposits occurring at Ina suggest that they were recently emplaced and that the Moon experienced small-scale, ongoing volcanic eruptions during the last 100 million years. The existence of young volcanism on the Moon, if confirmed, would indeed challenge our current notions of how the Moon is structured and how it evolved, an interpretation still vigorously debated. Because of the possibility for unique volcanic materials, Ina is a high-priority destination for future study, and determination of relatively recent volcanism at Ina and the other IMPs requires ground-truth. We assessed the geologic setting, scientific rationale, and several potential landing sites at Ina. We also developed a SmallSat-class lander design and mission architecture, along with a corresponding science payload, to address the top science objectives at Ina. We named the mission concept IMPEL (Irregular Mare Patch Exploration Lander). The primary objective of the IMPEL mission is to determine the presence and abundance of any sub-meter-scale fractures or pits in Ina's deposits that would inform their origins and age. Secondary objectives include characterizing Ina's composition and physical properties. The spacecraft configuration (named the Dual ESPA Module Planetary Lander, DEMPL) that we developed in this study employs two ESPA (Evolved Expendable Launch Vehicle, EELV, Secondary Payload Adapter) modules integrated with flexible tethers and bands. One of the modules is used to decelerate the spacecraft from direct lunar insertion and the other functions both as additional propulsion and as a detached lander containing most of the spacecraft subsystems and the science payload. Our novel spacecraft configuration provides a new mechanism for surface exploration in deep space using small-scale planetary landers. The lander is an adaptable platform that can deliver up to 9 kg of science payload to the lunar surface. This approach is very capable for deep space exploration at the small spacecraft scale, and it has the potential to provide access to the lunar surface using a low-cost, low-mass, affordable, simplified configuration. The Ina IMP is one of many possible destinations. Highlights: We present an innovative strategy to explore the Ina Formation with a SmallSat lander. The primary science objective is to determine the age and origin of Ina. Secondary science objectives include determining Ina's composition and quantifying volcanic contributions. Landing site analyses demonstrate the feasibility of achieving the science objectives at several sites.